Performance of capillary discharge guided laser plasma wakefield accelerator - Nakamura, K; Esarey, E; Geddes, C; Gonsalves, A; Leemans, W; Panasenko, D; Schroeder, C; Toth, C; Hooker, S (2007)
A GeV-class laser-driven plasma-based wakefield accelerator has been realized at the Lawrence Berkeley National Laboratory (LBNL). The device consists of the 40 TW high repetition rate Ti:sapphire LOASIS laser system at LBNL and a gas-filled capillary discharge waveguide developed at Oxford University. The operation of the capillary discharge guided laser plasma wakefield accelerator with a capillary of 225 μm diameter and 33 mm in length was analyzed in detail. The input intensity dependence suggests that excessive self-injection causes increased beam loading leading to broadband lower energy electron beam generation. The trigger versus laser arrival timing dependence suggests that the plasma channel parameters can be tuned to reduce beam divergence. ©2007 IEEE.